Pentingnya Pendidikan Agama Kristen Dalam Gereja Di Era Disrupsi - Paulus Suyatno (LOGON ZOES: Jurnal Teologi, Sosial dan Budaya, 2022)
The importance of Christian religious education in the church in the era of disruption is a primary need for God's church. Because the era of disruption challenges the church to innovate massively and fundamentally towards a new system. The era of disruption is an era of massive change, thus changing various systems and arrangements in new ways. The church must be ready to face the accelerated pace of technology in the era of disruption. This writing method is qualitative descriptive with literature studies and interviews. The purpose of this writing is for Pastors, administrators, church councils to apply Christian Religious Education in the church in the era of disruption in a progressive, intensive and collaborative manner without helping the growth of faith and loyalty of God's congregation. On the other hand, in the era of disruption, believers' faith grows stronger, tougher, stronger and more mature. The results of the writing are: the need for Christian religious education to be properly introduced to the church in the era of disruption and it is necessary to understand correctly the meaning of the importance of Christian religious education in the church in the era of disruption, both online and offline.Pentingnya Pendidikan Agama Kristen dalam Gereja di era disrupsi adalah sebagai kebutuhan primer bagi gereja Tuhan. Karena diera disrupsi menantang gereja untuk berinovasi secara besar-besaran dan mendasar kearah sistem yang baru. Era disrupsi merupakan era perubahan yang secara masif, sehingga mengubah berbagai sistem dan tatanan ke cara baru. Gereja harus siap menghadapi percepatan lajunya teknologi di era disrupsi. Metode penulisan ini kualitatif diskriptif dengan studi pustaka dan wawancara. Tujuan dari penulisan ini adalah supaya Gembala Sidang, pengurus, majelis gereja menerapkan Pendidikan Agama Kristen dalam gereja di era disrupsi secara progresif, intensif dan berkolaborasi tanpa membantutkan pertumbuhan iman dan kesetiaan jemaat Tuhan. Sebaliknya diera disrupsi tertumbuhan iman orang percaya semakin kokoh, tangguh, kuat dan dewasa. Hasil dari penulisan adalah perlunya Pendidikan agama Kristen   diperkenalkan secara benar kepada gereja di era disrupsi dan perlu dipahami, mengerti dengan benar arti pentingnya Pendidikan agama Kristen dalam gereja diera disrupsi dengan cara daring maupun luring.